Lava Dome Morphology and Viscosity Inferred From Data-Driven Numerical Modeling of Dome Growth at Volcán de Colima, Mexico During 2007-2009 - Zeinalova, Natalya; Ismail-Zadeh, Alik; Melnik, Oleg; Tsepelev, Igor; Zobin, Vyacheslav (Frontiers in Earth Science, 2021)
Magma extrusion, lava dome growth, collapse of domes, and associated pyroclastic flow hazards are among important volcanological studies. Using camera images of lava dome growth at Volcán de Colima in Mexico between early 2007 and fall 2009 and data-driven finite-volume numerical modeling, we study here the influence of the rheological properties of magma on lava dome morphology. Our viscosity model incorporates crystal growth kinetics and depends on the characteristic time of crystal content growth (or CCGT) and the crystal-free magma viscosity. Initially, we analyze how this viscosity, CCGT, and the rate of lava extrusion influence the morphology of the growing dome. Several model scenarios of lava dome growth are then considered depending on the crater geometry, the conduit location, the effective viscosity of dome carapace, and the extrusion rates. These rates are determined either empirically by optimizing the best fit between the morphological shape of modeled domes and that of the observed dome or from the recorded lava dome volumes. The maximum height of the modeled lava dome and its horizontal extent are in a good agreement with observations in the case of the empirically-derived extrusion rates. Due to the interplay between the lava extrusion and the gravity forces, the dome reaches a height threshold, and after that a horizontal gravity spreading starts to play an essential role in the lava dome evolution. It is shown that the crater topography is likely to be inclined toward the west. A thick, highly viscous dome carapace influences the dome morphology by retarding dome advancement and developing steep-sided eastern edge of the dome. The viscosity of the modeled lava dome (~1012 Pa s) is in a good agreement with the effective viscosity estimated experimentally from lavas of Volcán de Colima. The developed model can help in assessments of future effusive eruptions and lava dome growth at Volcán de Colima or elsewhere, and can be used to estimate stresses in dome carapaces and potential dome failures.